The practice of medicinal chemistry - Aldous, David (David John); Raboisson, Pierre; Rognan, Didier; Wermuth, C. G. (London : Elsevier Academic Press, 2015)
The Practice of Medicinal Chemistry, Fourth Edition, provides a practical and comprehensive overview of the daily issues facing pharmaceutical researchers and chemists. In addition to its thorough and excellent treatment of basic medicinal chemistry principles, this updated edition has been thoroughly revised to provide new and expanded coverage of the latest technologies and approaches in drug discovery. With in-depth coverage of high content screening, scoring, docking, binding free energy calculations, polypharmacology, QSAR, chemical collections and databases, and much more, this book is the go-to reference for all academic and pharmaceutical researchers who need a complete understanding of medicinal chemistry and its application to drug discovery and development
Note continued: XIV. Patent Information -- XV. Toxicology -- XVI. Meta-Sites and Technology Service Provider Databases -- XVII. Conclusion -- 36. Protection of Inventions in Medicinal Chemistry / Christopher Brice -- I. Patents and the Medicinal Chemist -- II. What Kinds of Medical Inventions can be Patented? -- III. The Basics of Patent Law -- IV. The Role of the Medicinal Chemist in the Patent Arena -- V. Patents as a Source of Scientific Information -- VI. Other Forms of Protection -- VII. Conclusion
Includes bibliographical references and index
1 13
Keywords: Drugs -- Design; Pharmaceutical chemistry; Chemistry, Pharmaceutical; Moderator; Pharmaceutical Preparations -- chemistry